An outstanding new species of Senna (Fabaceae: Caesalpinioideae) from southern Puebla, Mexico - Rojas-Martínez, Cecilia; Flores-Olvera, María Hilda; Ochoterena, Helga; Delgado-Salinas, Alfonso (Phytotaxa, 2019)
Senna acatlanensis is described and illustrated here. This species is restricted to a forest ecotone in southern Puebla (Mexico), and stands out by its unique large asymmetric flowers, with yellow petals that do not fade away to reddish-brown as they dry-out, heteromorphic and variable androecium; with four staminodes, ten or less fertile stamens; by its pendulous, cylindrical fruits, with chartaceous strigillose valves, and inter-seminal septa with a black-pulpy endocarp that surrounds exareolate seeds. These morphological attributes in addition to leaves with two pairs of leaflets, anthers with beaks, gynoecium multi-ovulated, and transversely oriented seed, turned broadside to the septa placed this new species within the series Bacillares. Illustrations, taxonomic comments, distribution and conservation status are provided with a key to the Mexican species of series Bacillares.